CGIAR Research Program on Policies, Institutions, and Markets: CGIAR Portfolio 2017-2022 Program Leaflet - CGIAR System Management Office (International Food Policy Research Institute, 2017)
Sound policies, robust institutions, and well-functioning markets complement new discoveries of agricultural science to create dynamic and resilient food systems. The combination of strong agricultural science and good policy is especially important in poor rural areas, where many people depend on farming for their livelihoods. Agricultural growth creates new jobs both on and off farms as rural economies diversify. Consumers benefit from more affordable food. Landscapes recover as farmers, fishers, herders, and forest dwellers adopt better management regimes and develop new institutions for collaborative governance.